The Effect of Price and Quality on The Decision to Purchase Onion Seeds at Ud Parewa Mulia - Mei Karlina; Muhajirin Muhajirin; Nur Khusnul Hamidah (PT. Anagata Sembagi Education, 2024)
Satisfying consumer needs is every company's dream. Apart from being an important factor for a company's survival, fulfilling consumer needs can increase its superiority over the competition. Consumers who are satisfied with price and quality tend to repurchase the product and reuse the product when the same need arises again in the future. This research aims to determine the influence of price and quality on the decision to purchase onion seeds at Ud Parewa Mulia. This research uses a quantitative approach with survey methods, while this type of research is included in associative research. The population in this study were consumers who had shopped for onion seeds at UD Parewa Mulia. The number of samples taken in this study was 50 respondents. The sample used in this research was purposive sampling. The research instrument used a questionnaire with a Likert scale. Data analysis uses multiple linear regression, correlation, determination test, partial analysis test with t test and f test (simultaneous). To test the influence between variables, use SPSS (Statistical Service Product Solutions) version 23.00. The research results based on the t test (partial) show that price influences purchasing decisions, quality influences purchasing decisions, and price and quality together influence purchasing decisions..